Hotelling under Pressure - Anderson, Soren T.; Kellogg, Ryan; Salant, Stephen W. (Journal of Political Economy, 2018)
We show that oil production from existing wells in Texas does not respond to oil prices, while drilling activity and costs respond strongly. To explain these facts, we reformulate Hotelling’s classic model of exhaustible resource extraction as a drilling problem: firms choose when to drill, but production from existing wells is constrained by reservoir pressure, which decays as oil is extracted. The model implies a modified Hotelling rule for drilling revenues net of costs, explains why the production constraint typically binds, and rationalizes regional production peaks and observed patterns of prices, drilling, and production following demand and supply shocks.